Synthèse Générale des entretiens réalisés à Manga - Tapsoba, Tatiana Nadine (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2022)
This text presents a general summary of the data collected in Manga as part of the research project. The actors interviewed were the Kaam Naaba (customary chief), the head of social services at the Manga House of Arrest and Correction (MACM), the children's judge, the Catholic chaplain at the MACM and the Balm Naaba (customary chief). These interviews focused on management types and procedures, types of punishment and their relationship with gender and social class. Community mediation mechanisms and the population's perception of the different types of punishment and judicial bodies (modern and traditional).
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Manga